Income Potential of Micro, Small and Medium Enterprises (MSMEs) in Financing Higher Education - Kuswanto Kuswanto; Muhammad Rohimin; Muhammad Arif Liputo (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2025)
Higher education plays an important role in improving the quality of life of families and supporting economic and social development. However, the high cost of education is an obstacle for MSME families, so that the main business income becomes the main factor in financing the education of family members. This study aims to analyze the potential household income of MSMEs in rural areas of Jambi Province, Indonesia, to support higher education costs at the University of Jambi. Using a quantitative descriptive method, this study involved 23 MSME families. The analysis was carried out by comparing the cost of higher education with the income allocated from the main and additional businesses. The results show a ratio of income to education costs of 0.4, meaning that income from the main business is not enough to finance family education. If income from additional businesses is calculated, the ratio increases to 1.08, indicating the family's potential to meet the cost of higher education. This finding emphasizes the importance of business diversification and increasing family income to be able to support higher education sustainably. It is recommended that MSME families develop businesses in other fields to increase income, while the government is expected to provide entrepreneurship training, access to financing, and business assistance. These efforts are expected to increase access to higher education for MSME families significantly and sustainably.